The effects of surface water availability on corn production in Weld County, Colorado - Worrall, Cortland (Kansas State University, 2024)
The agriculture industry in Colorado relies heavily on the amount of snowpack and surface water to be successful and to be profitable. In Colorado they use reservoirs and ditches to disperse water to farmers and the rest to other uses and cities. The amount of water that is allocated to a single farmer can vary from year to year due to unpredictability of availability of water from snowpack and rainfall. In addition, the state has seen multiple years of population growth that has caused more of the surface water to be allocated to the rapidly growing cities instead of to farmers for agriculture use. In this study, I focus on Weld County Colorado because it is the largest agriculture producing county in Colorado and one of the fastest growing counties in terms of population Colorado. This study will look at historical data of surface water used for irrigation and the effects it has on farmers and their decision to plant corn over the last thirty years. I study the impacts on corn because corn is a major crop in Weld County and needs significantly more water than some other crops. The surface water data will come from the Colorado’s Decision Support System (CDSS) that provides all the historical and current water levels of all the reservoirs and ditches. Corn data was collected from the United State Department of Agriculture (USDA) National Agricultural Statistic Service (NASS). This study examines the correlation between surface water available for agricultural irrigation use and the amount of corn planted that year and corn yield. A regression analysis is used in this study to see how the available surface water from year to year will affects farmers and their decision to plant corn and the yield. Other variables included in the analysis to help understand the correlation between surface water and corn production are temperature and precipitation.
Keywords: Colorado water; Regression analysis; Corn production; Irrigation; Planting decision; Water shortage